2020
DOI: 10.1177/1757743820932603
|View full text |Cite
|
Sign up to set email alerts
|

Ideological disempowerment as an effect of neoliberalism on teachers

Abstract: In works based on deprofessionalisation/proletarianisation theory, teachers are described by researchers as technically disempowered because of the entry of neoliberalism into the institutional environment of education. Technically disempowered teachers suffer not only from work stress but also from other kinds of negative emotional experiences. This article contributes to deprofessionalisation/proletarianisation theory by introducing the concept of ideological disempowerment to explain why teachers complain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
6
0
4
Order By: Relevance
“…In this sense, the STEM teachers may interpret the cases of students' growth as the results of their efforts exerted on the STEM educational work leading to a sense of achievement or positive self-concept that arouse intense positive emotions. However, the literature has suggested that teachers find it difficult to sustain positive emotions in the context of educational accountability because such accountability may intensify administrative work, leading teachers to devalue the educational values of their work and displace them with administrative values, resulting in difficulties for teachers in understanding the meaning of their work [17,18,21,[59][60][61][62][63]. Although the findings implied that teachers must manage a heavy administrative workload for STEM educational work for accountability purposes, they still feel positive about the work.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the STEM teachers may interpret the cases of students' growth as the results of their efforts exerted on the STEM educational work leading to a sense of achievement or positive self-concept that arouse intense positive emotions. However, the literature has suggested that teachers find it difficult to sustain positive emotions in the context of educational accountability because such accountability may intensify administrative work, leading teachers to devalue the educational values of their work and displace them with administrative values, resulting in difficulties for teachers in understanding the meaning of their work [17,18,21,[59][60][61][62][63]. Although the findings implied that teachers must manage a heavy administrative workload for STEM educational work for accountability purposes, they still feel positive about the work.…”
Section: Discussionmentioning
confidence: 99%
“…Due to pro-performative reforms, teachers experience tensions in their professional life consequently causing a sense of estrangement (Meng, 2009). Neoliberalism encourages rational choice, ultra-individualism and competition, therefore deemphasizing the role of emotions and care in the process of teaching (Tsang and Qin, 2020). Through a qualitative engagement with school teachers, it was found that top-down leadership regimes are the main cause of alienation (Brooks et al, 2008).…”
Section: Teacher Alienationmentioning
confidence: 99%
“…For example, some teachers experienced alienation due to excessive non-teaching work which lacks an educational and creative value forced on them in the institution ( Tsang, 2016 ). Another source of alienation lies in the inability of teachers to find meaningful pedagogical value in “non-instructional work” implicated due to neoliberalism by encouraging a non-pedagogical role of teachers ( Tsang and Qin, 2020 ). Levinsson, Norlund and Beach (2020) , argue that neoliberalism has turned pedagogical actors into “Alignment Slaves” and “Audit Puppets,” which reflect existential displeasure experienced by the teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers as laborers are subjected to a heist of their professional time and judgement. Under neoliberalism, ideologically disempowered teachers hold a narrow concept of learning in which extreme standardization and accountability measures discourage them from prioritizing the whole-person growth of students (Pinto, 2015;Tsang & Qin, 2020). Deliverology imposes external accountability on teachers' work, contributing to deprofessionalization and disempowerment.…”
Section: Teacher Professionalism and The Heistmentioning
confidence: 99%